2019
DOI: 10.1149/2.0061909jes
|View full text |Cite
|
Sign up to set email alerts
|

ABE-Stat, a Fully Open-Source and Versatile Wireless Potentiostat Project Including Electrochemical Impedance Spectroscopy

Abstract: Exciting discoveries in material science and molecular interactions are resulting in many promising electrochemical biosensor technologies. Compact, high-quality instrumentation is critical to adaptation of these new technologies especially for distributed applications in the agriculture and food industries. To this end, we have developed ABE-Stat, a fully open-source, battery-powered potentiostat project including a wireless Android interface. ABE-Stat is capable of conducting routine electrochemical analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 55 publications
2
65
0
1
Order By: Relevance
“…Calibration with the handheld potentiostat developed by Jenkins et al [ 29 ] is shown in ( Figure 4 E,F). The device connects to a smartphone or tablet via Bluetooth, and the data are formatted as a csv file that can be analyzed off line [ 29 ] or autonomously using support vector machine learning [ 34 ], as shown in our previous work.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Calibration with the handheld potentiostat developed by Jenkins et al [ 29 ] is shown in ( Figure 4 E,F). The device connects to a smartphone or tablet via Bluetooth, and the data are formatted as a csv file that can be analyzed off line [ 29 ] or autonomously using support vector machine learning [ 34 ], as shown in our previous work.…”
Section: Resultsmentioning
confidence: 99%
“…All clean room work was conducted at the Aggiefab facility at Texas A&M University (College Station, TX, USA). A CHI 600E potentiostat (Austin, TX, USA) with CHI6044e software or handheld potentiostat (ABE-STAT [ 29 ]) with Samsung Galaxy tablet was used for electrochemical analysis as noted. A Bruker Dektak Profilometer (Tucson, AZ, USA) was used to quantify electrode features.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low-cost, portable, mobile phone-based acquisition systems have been developed for mercury analysis in the field [100]. While this is significant for deploying sensors in low-income regions, the inexpensive-portable sensor-systems lack data analytics capability to transform the data into meaningful information that could be useful for the user.…”
Section: Alerting Mercury Exposure In Artisanal Gold Mining Communitiesmentioning
confidence: 99%